Strategi Inovasi Produk dalam Menghadapi Persaingan Usaha Home Industri - Junaedi, Deddy; Aini, Lutfiyah Qilfa Khoiril; Nurhalisa, Siti; Rustina, Siti Ayu; Handayani, Ririn Yanti; Jannah, Lailatul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research explores the product innovation strategies implemented by the home-based business "Boss Gedhank" in response to increasing competition in the local snack industry. Located in Sumberanyar Village, Boss Gedhank specializes in banana chip products with unique flavor innovations such as spicy-sweet variants made from local spices. The business also diversified into spicy noodle products under the "Bos Pedas" label. Using a qualitative descriptive approach, data were collected through purposive sampling, interviews with business owners and employees, direct observation, and documentation. The findings indicate that product innovation is the core strategy used to enhance competitiveness. This includes the creation of new product variants, leveraging digital marketing platforms such as Shopee and TikTok to expand market reach, and paying close attention to aesthetic packaging design. These innovations have succeeded in attracting a wider range of consumers and maintaining product appeal despite external challenges such as rising raw material costs and limited availability of certain banana types. The study concludes that consistent innovation, responsiveness to market trends, and strong branding through visual appeal are crucial for sustaining growth in the competitive home industry sector. Boss Gedhank's ability to adapt and evolve has enabled it to strengthen its position and gain a competitive edge in the local food market.